Development of augmented reality-based interactive space media for 5th grade elementary school students - Triwahyuningtyas, Dyah; Ningrum, Siska Widyana; Suastika, I Ketut; Azizah, Nurul (Jurnal Bidang Pendidikan Dasar, 2025)
This research is motivated by the lack of interactive learning media in schools. The study aims to determine the feasibility of Augmented Reality-based interactive space building media using the Assemblr EDU application for 5th grade elementary students. This development research applies the ADDIE model with data collected through observation, interviews, documents, and questionnaires. The research subjects involved 14 students from SDN Sukun 1 Malang. The study focuses on the feasibility aspect based on expert validation. The results show that media experts gave a feasibility percentage of 98% in the "Very Feasible" category, while material experts gave 75% in the "Feasible" category. These results indicate that the Augmented Reality-based interactive media is appropriate for use in elementary school learning, meeting feasibility standards and offering potential to support engaging and effective learning experiences for students.